Examining authorship in publications in selected health professions education journals - Anusmriti Guragain; Pathiyil Ravi Shankar; Ian G. Wilson (Academia Medicine, 2024)
The distribution of publications in selected health professions education (HPE) journals according to the income status of the country where the first author was located during the period from January 2020 to December 2022 was studied. The Scopus quartile one (Q1) journals Academic Medicine, BMC Medical Education, Medical Education, Medical Education Online, Medical Teacher, and Teaching and Learning in Medicine were examined. The year of publication, the type of article, and the income status of the country of the first author were noted. Instances where the first and the corresponding author were the same and different were noted. There were 5,714 unique articles published. There were 26 instances where the first author had multiple affiliations in countries of differing income levels, and the articles were duplicated/triplicated providing a total of 5,740 articles. Most articles (87%) were published by authors from high-income countries and only 0.8% were from low-income countries, with the remainder from middle-income countries. BMC Medical Education had the maximum percentage of authors from low- and middle-income countries. Nations having most of the world’s population and medical schools are significantly underrepresented in publications in the assessed journals impacting diversity and inclusivity in HPE publishing. This is a matter of concern requiring further studies.